2020
DOI: 10.1186/s12957-020-02029-w
|View full text |Cite
|
Sign up to set email alerts
|

Whether stoma support rods have application value in loop enterostomy: a systematic review and meta-analysis

Abstract: Purpose The purpose of the systematic review and meta-analysis is to analyze the application value of the stoma support rods in loop enterostomy. Methods The studies on the application of stoma rods in loop enterostomy published from January 2000 to January 2020 were searched in the databases of PubMed, Embase, Cochrane library, and Clinical trials. All randomized controlled trials (RCTs) and cohort studies that observed the value of stoma rods were included according to inclusion criteria. The RevMan5.3 sof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The use of a rod (in loop stomas) does not seem to reduce the rate of SR. In a review of 1131 stoma patients, the rate of SR in the rod group was not significantly lower than the rate recorded in patients without rod (2.3% vs 3.4%) [ 41 , 48 ].…”
Section: Methodsmentioning
confidence: 93%
See 2 more Smart Citations
“…The use of a rod (in loop stomas) does not seem to reduce the rate of SR. In a review of 1131 stoma patients, the rate of SR in the rod group was not significantly lower than the rate recorded in patients without rod (2.3% vs 3.4%) [ 41 , 48 ].…”
Section: Methodsmentioning
confidence: 93%
“…In this context, as recently reported by a Chinese systematic review and meta-analysis, a demonstrated risk factor for the occurrence of a MCS is stoma support rods, which seems to double the risk of MCS if compared with ostomy created without using rod. An alternative option to standard rods, without significantly increasing the rate of MCS, is skin bridge which seems to be associated with a rate of MCS significantly lower than traditional rods [ 41 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Enterostomy is the basic operation of colorectal surgery [10] .At present, there are few researches and literatures about enterostomy skills at home and abroad, and most of the information about enterostomy found by search engine focuses on the research of nursing after enterostomy.Most enterostomy experience needs to be accumulated slowly from clinical operation and observation.Professor Du R doesn't recommend the routine use of stoma support bar, which not only does not reduce the incidence of stoma retraction, but signi cantly increases the incidence of stoma necrosis, dermatitis around stoma and separation of skin and mucosa [11] .Su Hao and other scholars believe that continuous suture of intradermal seromuscular layer for enterostomy is safe and feasible, and the short-term effect is satisfactory [12] .Some scholars even tried to apply 3D printing technology for suture-free colostomy [13] .An improved enterostomy technique summarized by the medical team is to complete the enterostomy by the needle-thread retained stitch.The main difference between the needle-thread retained stitch and thread and the traditional intermittent stitch is that the peritoneum, the posterior sheath and the anterior sheath of rectus abdominis muscle are sutured intermittently for one circle, then retain the needle and thread. Lift the intestinal tube out of the abdominal wall through the incision, and then use the retained needle and thread to sew and x the intestinal tube with the abdominal wall for a circle.The step-by-step suturing sequence simpli es the operation of enterostomy, and allows the operator to not only nish the suturing of peritoneum, anterior sheath and posterior sheath of rectus abdominis, but also easily nish the suturing and xing of intestinal tube and abdominal wall under the condition of small incision and small surgical eld.…”
Section: Discussmentioning
confidence: 99%
“…Stoma rods are used traditionally to prevent retraction of loop stoma into the abdominal cavity. But recent systematic reviews and meta-analyses have already showed that stoma rods do not reduce the incidence of stoma retraction and instead lead to increased rates of stoma-related complications 9 , 10 .…”
Section: Introductionmentioning
confidence: 99%